THERMOMAGNETIC ANALYZES OF SOILS FROM THE HYDROCARBON FIELDS - Menshov, O.; Kuderavets, R.; Popov, S.; Homenko, R.; Sukhorada, A.; Chobotok, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper we continue the studying of possible usage of the soil magnetism at the hydrocarbon prospection. It is occurred that more additional soil magnetic data should be used to improve the interpretation of material obtained. This paper discusses the application of the thermomagnetic analysis of soil samples from the territory of hydrocarbon deposits to clarify the magnetic mineralogy and its temperature changes. Starunia hydrocarbon field is lected for studying as an example, because of previous investigations of magnetic susceptibility of soils available as well as magnetic and geochemical survey works carried out in this area. The new results of thermomagnetic soil analysis are presented in this paper. For possible comparative discussion and interpretation we also used the results of the thermomagnetic analysis of soil samples from the oil and gas deposit of Venezuela. Thermomagnetic analysis is important method for determining the magnetic minerals, which form the magnetic properties of soils over the hydrocarbon field. We suggested that the ferrimagnetics are often the combination of the pedogenic minerals and authigenic magnetic phases, which are formed under the influence of hydrocarbons. Complex association of magnetic minerals are identified in the soils of oil and gas field Starunia. The iron sulphides like pyrrhotite phase are occurred in all soil samples, with magnetite being commonly found in all sample varieties. Moreover, temperature changes of magnetic susceptibility, which can be interpreted as a phase transitions of maghemite-hematite are also observed. The domain state has anapparent influence onto the thermomagnetic curves too, that could be the result of transition from the ultrafine single domain state (SD) under the room temperature to the superparamagnetic state (SP) at heating. Comparison between results of investigations of Ukrainian and Venezuela soil samples made it possible to conclude about the presence of the magnetite phase in both areas. At the same time, if the magnetite is the only ferromagnetic mineral identified in Venezuela, the Ukrainian soils are characterized by much more various authigenic mineralogical composition.
Keywords: magnetic susceptibility; Curie temperature; soil; hydrocarbons